Medical ethics in the light of maqāṣid al-Sharīʿah: a case study of medical confidentiality - Ghalia, Bouhedda; Amanullah, Muhammad; Zakariyah, Luqman; Muhsin, Syed Muhammad (IIUM Press, International Islamic University Malaysia, 2018)
The Islamic jurists utilized the discipline of maqāṣid al-sharīʿah, in its capacity as the philosophy of Islamic law, in their legal and ethical interpretations, with added interest in addressing the issues of modern times. Aphoristically subsuming the major themes of the Sharīʿah, maqāṣid play a pivotal role in the domain of decision-making and deduction of rulings on unprecedented ethical discourses. Ethics represent the infrastructure of Islamic law and the whole science of Islamic jurisprudence operates in the light of maqāṣid to realize the ethics in people’s lives. Scrutinizing the key themes of maqāṣid-based ijtihād and scope of ethics in maqāṣid, this article delves into the discourse on the application of maqāṣid to medical ethics. As a case study, this research analyses the extent of medical confidentiality in the light of maqāṣid and arrives at the conclusion that limited confidentiality goes more in line with the maxims of maqāṣid.